PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI DAN KEPUASAN KERJA (Studi pada Kasubag di Lingkungan Universitas Brawijaya Malang) - Wijaya, Jarot Ilhami; Hamid, Djamhur; Utami, Hamidah Nayati (Profit: Jurnal Adminsitrasi Bisnis, 2017)
In the modern organization, leadership will influence the behavior of employees in performing their duties. Job satisfaction change efforts require the participation of the leadership and all employees, it would also be achieved if there is the willingness and ability of each individual employee. This study aimed (1) to identify and explain the influence of leadership on employee motivation, (2) to identify and explain the influence, leadership on work motivation on employee job satisfaction. The research was conducted at Brawijaya University with 95 employees sampled. The statistical methods used to test the hypothesis is path analysis. Improved employee motivation preceded by the proper application of good leadership on task behavior and relationship. High job satisfaction necessary for excellent service or high quality services can be held. The data of this study to get some important conclusions that leadership is very important for employees in an effort to improve employee job satisfaction both directly and indirectly.Â Â